the The Effect of Non-Nutritive Sucking on the Pain Response and Pulse Frequency of LBW Babies During Infusion Installation in the NICU Room at RSD Mangusada: The Effect of Non-Nutritive Sucking on the Pain Response and Pulse Frequency of LBW Babies During Infusion Installation in the NICU Room at RSD Mangusada - Megantini, Ni Putu; Triana, Komang Yogi; Yunita Sari, Ni Luh Putu Dian (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2024)
Bayi berat lahir rendah membutuhkan pertolongan dengan perawatan intensif dan seringkali mendapatkan tindakan invasif salah satunya pemasangan infus. Hal tersebut dapat menimbulkan nyeri sehingga dapat mempengaruhi stabilitas kardiovaskuler salah satunya peningkatan frekuensi nadi. Penatalksanaan yang dapat dilakukan untuk mengatasi hal tersebut salah satunya non nutritive sucking. Penelitian yang telah dilakukan bertujuan untuk mengetahui adanya pengaruh non nutritive sucking terhadap respon nyeri dan frekuensi nadi bayi BBLR saat pemasangan infus di ruang NICU RSD Mangusada. Penelitian dilaksanakan dengan rancangan Post-test Only Control Group Design yang dilaksanakan pada bulan September sampai Oktober 2023 dengan Jumlah sampel 32 responden di bagi menjadi 16 responden kelompok perlakuan dan 16 responden kelompok kontrol yang dipilih dengan teknik Purposive sampling. Data dikumpulkan menggunakan Kuesioner Neonatal Infant Pain Scale dan alat oksimetri. Data dianalisis menggunakan uji Mann Whitney. Hasil penelitian rata-rata respon nyeri pada kelompok perlakuan menunjukkan hasil lebih rendah dibandingkan kelompok kontrol yaitu mencapai 2.56, begitu juga rata-rata nadi kelompok kontrol menunjukkan hasil yang lebih rendah yaitu mencapai 136 x/menit. Hasil analisis pengaruh non nutritive sucking terhadap respon nyeri dan frekuensi nadi Bayi berat lahir rendah saat pemasangan infus didapatkan nilai p value <0,001, sehingga dapat dikatakan terdapat pengaruh non nutritive sucking terhadap respon nyeri dan frekuensi nadi Bayi berat lahir rendah saat pemasangan infus. Rekomendasi penelitian ini diharapkan menjadi masukan bagi perawat sebagai pilihan memberikan non nutritive sucking pada bayi berat lahir rendah untuk mengontrol nyeri saat prosedur invasif. Kata Kunci: BBLR, Nadi, Non-nutritive sucking, Nyeri Low birth weight neonates require intensive care and are usually subjected to invasive treatments such as IV instillation. This can cause pain and have an effect on cardiovascular stability by increasing pulse frequency. Non-nutritive sucking is one of the treatments available to help with this. The research that has been conducted aims to determine the effect of non-nutritive sucking on the pain response and pulse frequency of LBW babies during infusion installation in the NICU room of Mangusada Hospital. The study was conducted using a Post-test Only Control Group Design from September to October 2023, with a sample size of 32 respondents divided into 16 treatment group respondents and 16 control group respondents chosen using a purposive sampling technique. The Neonatal Infant Pain Scale Questionnaire and an oximetry equipment were used to collect data. The Mann Whitney test was used to examine the data. The results of the median pain response study in the treatment group showed lower results than the control group, reaching 2, as well as the median pulse of the treatment group showed lower results than the control group, reaching 136.5 x/min. The analysis of the effect of non-nutritive sucking on the pain response and pulse frequency of low birth weight babies during infusion yielded a p value of 0.001, indicating that non-nutritive sucking had an effect on the pain response and pulse frequency of low birth weight babies during infusion. It is intended that this research recommendation will provide input for nurses as an option to provide non-nutritive sucking to low birth weight babies to control pain during invasive procedures. Keyword: LBW, Non-Nutritive sucking, Pain, Pulse